Digital Transformation and Artificial Intelligence in Marketing for Startups Using a Customer Knowledge Management Approach - Syech Idrus; Kamalina Din Jannah; Muhammad Bagus Adi Wicaksono; S. M. Parulian Tanjung; Fakhry Amin (International Journal of Artificial Intelligence Research, 2022)
Startups that need a comprehensive approach to managing Knowledge Management (KM) in a digital context face a significant challenge in taking advantage of the opportunities presented by digital transformation and artificial intelligence (AI) technologies, which are reshaping marketing organizations. There is a pressing need for more strategic marketing expertise to drive business value creation, and digital transformation and AI technologies offer great promise to help businesses overcome obstacles, challenges in practical application, and this shortage. In this paper, we take a resource-centric look at a central question: how can young companies with few resources and few employees push digital transformation in marketing forward? Integrating the methods of Knowledge Management and Customer Relationship Management (CRM), as in Customer Knowledge Management (CKM), can be crucial to achieving this objective. This study uses a qualitative approach with descriptive methods to analyze the research results. This research reveals that companies with limited capabilities and resources can still adopt technological developments in conducting marketing. Marketing departments can benefit from the big data that AI provides by mining it for useful customer insights that can be used to bolster customer relationship management strategies. Organizational factors such as customer focus, a culture of collaboration and knowledge sharing, strategy and support from top management, an organized structure, and the integration of functions are crucial to the success of CKM in the business.